Between Sound and Speech: Liminal Signs in Interaction. Issue 1 (2nd January 2020) - Dingemanse, Mark
ABSTRACT: When people talk, they recruit a wide range of expressive devices for interactional work, from sighs, sniffs, clicks, and whistles to other conduct that borders on the linguistic. These resources are used in the management of turn and sequence and the marking of stance and affect, and they represent an aspect of the interactional machinery that is as elusive as it is powerful. Phenomena long assumed to be beyond the purview of linguistic inquiry emerge as systematically deployed practices whose ambiguous degree of control and convention allows participants to carry out subtle interactional work without committing to specific words. While these resources have been characterized as nonlexical, nonverbal, or nonconventional, I propose that they are unified in their liminality: They work well precisely because they equivocate between sound and speech. The empirical study of liminal signs shows the promise of sequential analysis for building a science of language on interactional foundations.